Tibetan wa-zur and Laufer’s law - Jacques, Guillaume (2024)
Laufer’s law, according to which proto-Tibetan *-wa monophthongized to -o in Old Tibetan, is almost universally accepted. However, Hill (2006) pointed out that this law seems to be contradicted by the existence of a genuine -wa rhyme in Old Tibetan: unless Old Tibetan -wa has a distinct origin, the sound law *-wa > -o cannot be valid. The present article proposes a simple solution to Hill’s counterargument: Old Tibetan -wa comes from the fusion of two syllables.